COVERAGE OF POLITICAL PROCESSES IN TURKESTAN IN THE XIX CENTURY ON THE PAGES OF THE JADID PRESS - Olimova Zulfiyakhan Ibrahimjan kizi (Ethiopian International Journal of Multidisciplinary Research, 2025)
This article contains information about the coverage of political processes in Turkestan in the XIX century on the pages of the jadid press. Also, the existing newspapers of this period, articles of varying content published in them, talk about the change and reforms in the political life of that time. Articles published in the newspapers” great Turkestan“,” El flag " were also commented on.